2019
DOI: 10.14198/jhse.2020.154.09
|View full text |Cite
|
Sign up to set email alerts
|

Activity profiles of elite netball umpires: A review

Abstract: This review has outlined the existing literature relating to activity profiles in elite netball umpires. In particular, the physical (distance travelled), physiological (heart rate), and technical (movement classifications) characteristics have been described. The limited available literature report that on average elite netball umpires travel approximately 3850 m during a 60 min match. Up to approximately 50% of the match is spent standing, with only around 25% of the match in higher intensity movements such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Single refereeing decisions can have major impact on the outcome (Dosseville et al, 2013;Hossner et al, 2019;Raab et al, 2019), and accurate decisionmaking (DM) performance is considered to be one of the most important characteristics that a referee should possess (Bar-Eli et al, 2011;Nabli et al, 2019). Ample research has been conducted to identify sources of referees' bias, and to reveal how accuracy of officiating can be improved (Dohmen and Sauermann, 2016;Morgulev et al, 2018;Schweizer et al, 2013;Spencer et al, 2020). Contributing factors that have been found to assist referees in their DM processes include physical fitness (Helsen and Bultynck, 2004;Leicht, 2008), perceptual ability (Helsen and Bultynck, 2004;Kittel et al, 2019;Cobanoglu et al, 2021), mental ability (Anshel et al, 2014;Castillo et al, 2017), visual attention (Pietraszewski et al, 2014;Spitz et al, 2018), rules knowledge, and game management (Mascarenhas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Single refereeing decisions can have major impact on the outcome (Dosseville et al, 2013;Hossner et al, 2019;Raab et al, 2019), and accurate decisionmaking (DM) performance is considered to be one of the most important characteristics that a referee should possess (Bar-Eli et al, 2011;Nabli et al, 2019). Ample research has been conducted to identify sources of referees' bias, and to reveal how accuracy of officiating can be improved (Dohmen and Sauermann, 2016;Morgulev et al, 2018;Schweizer et al, 2013;Spencer et al, 2020). Contributing factors that have been found to assist referees in their DM processes include physical fitness (Helsen and Bultynck, 2004;Leicht, 2008), perceptual ability (Helsen and Bultynck, 2004;Kittel et al, 2019;Cobanoglu et al, 2021), mental ability (Anshel et al, 2014;Castillo et al, 2017), visual attention (Pietraszewski et al, 2014;Spitz et al, 2018), rules knowledge, and game management (Mascarenhas et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a descriptive analysis of netball players or even the umpires of this sport (Spencer, McErlain-Naylor, Paget, & Kilding, 2019). Investigations have reported normative data for physical parameters and physiological characteristics of netball players according to their position (Thomas et al, 2019), level of performance and categories (Sinclair, Coetzee, & Schall, 2020;Thomas, Thomas Ismail, Comfort, Jones, & Dos'Santos, 2016) and even the umpires of this sport.…”
Section: Introductionmentioning
confidence: 99%